ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MASYARAKAT KECAMATAN MEDAN HELVETIA DALAM MEMILIH LEMBAGA KEUANGAN SEBAGAI SUMBER PENDANAAN - Denisa Irawaty Nababan; Haroni Doli Ritonga (Departemen Ekonomi Pembangunan USU, 2013)
The purposes of this research is to analyze the factors that influence the decision of the societies of Medan Helvetia District in choosing financial institutions as a source of funding. The data obtained from 60 respondents that customers who obtain financial resources or obtain creditfrom a bank loan, bank SUMUT and Bank Rakyat Indonesia (BRI) branches Medan Helvetia, by taking simple random sampling technique. The method of analysis is descriptive analysis. The results showed that the rate of interest, system administration, collateral, and credibility of afinancial institution have significant impact on the community in selecting financial institutions as a source of funding in the district of Medan Helvetia. Keywords : financial institutions, sources of financing, interest rates, system administration, collateral, credibility